New Stable Control Structure for Nonlinear Systems: A Case Study of an Induction Motor Drive - Pavol Fedor; Daniela Perdukova; Peter Bober; Marek Fedor (Science and Technology: Developments and Applications Vol. 1, 2024)
Induction motors (IMs) are robust, reliable, and widely used in industrial applications due to their low cost and minimal maintenance requirements. However, their control poses challenges, as it requires complex circuitry to handle variable frequency, intricate dynamics, and parameter variations. This article presents the design and experimental validation of a continuous nonlinear control system based on a novel control structure that utilizes a linear reference model. By applying Lyapunov’s second method, the proposed structure ensures asymptotic stability. The key innovation in this control design lies in the use of an additional state variable, which enhances system information and control effectiveness. This structure is implemented for the angular speed control of an induction motor (IM) drive a complex higher-order nonlinear system. The developed control algorithm achieves zero steady-state deviation in the IM drive’s angular speed. Simulations and experiments across various operating conditions demonstrate the advantages of this new control structure. In addition to achieving the desired dynamics, the method ensures system stability, invariance to disturbances, and robustness against parameter variations. Compared to traditional vector control methods for IM drives, the proposed structure is simpler, does not require precise knowledge of system parameters, and avoids stability issues. The controller is suitable especially for any drive system including control of robotic systems control having a precise hierarchical control structure. Therefore, its broad utilization in industrial applications can be assumed. This approach promises broad applicability not only in systems with IM drives but also in a variety of industrial control applications.